رحمت عالم ﷺ کی غیر مسلم محسنین کی احسان شناسی: The Prophetic Conduct of reverence with Non-Muslims - Dr.Yasin Mazhar Siddiqui (Seerat Studies, 2023)
The basis of reverence for Humanity on humanitarian grounds is not only found in the Holy Quran but is also evident in the Seerah of the Prophet peace be upon him. A study of his life and conduct with the non-Muslims in this context has been carried out in this article. The author examines the dimensions of the Prophetic Conduct based on the humanitarian grounds with the non-Muslims and provides its evidences from the life of the prophet. This aspect of the prophetic model is not only analyzed in the Makkan or pre migration era but the author provides ample evidences of it from the Madinian era. The Prophetic Model of Conduct with the non-Muslims is again analyzed in different scenarios such as war, peace, hospitality, and social welfare, protection of the wealth, life and honor. The paper holds a significance in the current scenario and provides sound grounds for the basis of reverence for Humanity on humanitarian grounds from the prophetic model ..